PTU-156 Cost and availability of gluten-free foods in the uk: in store and online. (22nd June 2015) - Burden, M; Mooney, PD; Blanshard, R; White, W; Cambray-Deakin, D; Sanders, DS
Abstract : Introduction: Coeliac Disease (CD) is an autoimmune condition of the small bowel. A gluten-free (GF) diet is the only treatment for CD and with increasing incidence, 1 the demand for GF food has increased. Prior studies show GF food is more expensive and high street availability is limited. 2 However this has not been assessed for online GFD. We aimed to assess the availability and cost of GF foods across a range of supermarkets in a single UK city (Sheffield). We also aimed to assess the impact online retailers had on the GF food market. Method: 67 supermarkets were analysed, including a range of categories, sizes and locations. The total number of GF items which were on sale was counted and 10 items were selected to represent a range of commonly bought GF foods for which the price and availability was recorded. Where any were found, the price of their gluten-containing counterpart was also recorded. The same factors were then used to assess online retailers. Results: Of the 67 supermarkets visited, 27 (40.3%) stocked no GF items, with the remaining 40 (59.7%) stocking at least one. The mean number of GF items sold per store was 30, but this varied greatly by store category and size. None of the budget or corner supermarkets surveyed stocked any GF items. Regular and luxury supermarkets had a greater range (p < 0.0001), stocking 37 and 55 items on average respectively, as did larger supermarkets in general (p < 0.0001). In terms of the ten items specifically surveyed, 31 (46.3%) stores stocked none of the items, with the remaining 36 (53.7%) stocking at least one. Stores that stocked GF food had a median of 8 of the 10 specific items available. Overall, GF items cost significantly more than their gluten-containing counterparts, with GF items costing on average 4.1 times more (p < 0.0001). All 21 online stores surveyed sold at least one GF item. The average number of GF items sold was 609, compared with 30 for stores (p < 0.001). The proportion of highlighted items sold was also significantly higher, with an average of 73.3% sold (p < 0.001). Despite a larger range, the average cost of GF items online was higher than in stores. Conclusion: The availability of GF food in budget supermarkets and corner shops is lacking and GF food remains significantly more expensive. The greatest availability is online and in larger regular/luxury supermarkets. The issue remains that this could prevent lower socioeconomic groups from fully adhering to a GF diet. Disclosure of interest: M. Burden: None Declared, P. Mooney: None Declared, R. Blanshard: None Declared, W. White: None Declared, D. Cambray-Deakin: None Declared, D. Sanders Consultant for: Has received funding from Dr Schar a gluten free food manufacturer for investigator led studies into coeliac disease. References: West J, et al . Incidence and prevalence of celiac disease and dermatitis herpetiformis in the UK over two decades: Population-Based study. Am J Gastroenterol. 2014;109:757–768 Singh J, Whelan K. Limited availability and higher cost of gluten-free foods. J Hum Nutr Diet 2011;24:479–486